The gender wage gap in New Zealand : theory and evidence : a thesis presented in partial fulfilment of the requirements for the degree of a Master of Business Studies at Massey University - Summers, Stephen Michael (Massey University, 1999)
This thesis focuses on the issue of the gender wage gap in New Zealand that has been a prevalent topic in most countries and in a variety of academic circles over recent decades. Those who conclude that females are still being discriminated against in the labour market point to the use of a combination of policies, such as affirmative action and comparable worth, as a possible solution. Opponents to this view contend that there are many reasons that, combined, explain why females often earn less than their male counterparts. This thesis, encompassing a variety of statistics, illustrates that females have made, and continue to make, strong progress in all facets of the labour market. Thus, in conclusion, legislation to introduce new policies to narrow any gap is a road fraught with too many dangers and one that we do not need to go down.
Keywords: Pay equity; Women; Sex discrimination in employment; Employment; New Zealand